Biomimetic heterogenous elastic tissue development - Kai Jen Tsai (Nature Portfolio, 2017)
3D Printing Artificial Elastic Tissues Solvent-free thermoplastic polyurethanes (TPU) could be used to 3D-print artificial tissues saving time and money. Achala de Mel and colleagues at University College London used open-source 3D-modelling software and commercially available 3D printers to fabricate a bespoke tracheal stent from custom-made TPU. The team was able to control the material’s porosity with 3D-design, which could facilitate its vascularisation if implanted. The trachea was mechanically and structurally similar to that of an adult, showing longitudinal elasticity and radial rigidity. When attached to a ventilator system, it responded well to pressures similar to those of inspiration, forced expiration, coughing or crying. 3D-printed trachea was treated with bioactive molecules so cells could potentially adhere to and proliferate on its surface. This method could be used to fabricate bespoke elastic tissue substitutes, avoiding costly and time-consuming cell-culture techniques.